The Evolution of Interlocking Directorates Studies - A Global Trend Perspective (2019)
Directors’ corporate networks have been the subject of several studies that explore their different consequences, such as resource collaboration, transmission of practices, financial decisions, reduction of uncertainty, control and management, the firm’s reputation and individual interests. However, there is still no consensus about what these interlocking directorates (IDs) really do for firms and in what direction current research is following. This study carried out an extensive review of the literature in 75 papers (from 1969 to 2018) focused on IDs research, and as a result proposes two categories and four subcategories related to companies’ outcomes. The study found that the biggest contribution to firms, focuses on the description of network structures and control and management results, remarking the difference between North America IDs research and other regions, while shedding light on what IDs do for firms. It also identified gaps in research such as dissemination, globalization and collusion that need to have more analysis.